Números racionais na forma fracionária: atividades para superar dificuldades de aprendizagem - Lima, Fernanda Soto (2013)
This dissertation presents the development of activities related to the teaching of rational numbers in fractional form so diverse and unique to the teacher and the students, through the exploitation of that content with manipulatives - construction of a fractional fractal card, use graph paper and in particular the construction of a curtain fractional color to the classroom - made in mathematics classes in 6th grade C Elementary School II of the afternoon, in order to show the importance and use of mathematical theory combined with practice. Highlights the importance of the teaching of mathematics, a brief history of the use of fractions in ancient Egyptian civilization and the construction of an instructional sequence based on the Didactic Engineering. Describes the steps for implementing the instructional sequence, its development in the classroom and conclusions pointing out that the use of manipulatives improves understanding of concepts related to rational numbers in fractional form. It also presents design variations, which can be developed by teachers in Elementary and High School.